2018
DOI: 10.1016/j.margeo.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Climate forcing of regionally-coherent extreme storm impact and recovery on embayed beaches

Abstract: The effective management of sedimentary coastlines demands a good understanding of the seasonal and inter-annual cycles in beach volumes, as well as the potential impact of extreme events. This paper uses a 10-year time series (2007-2017) of supra-and intertidal beach volume from exposed and cross-shore transport-dominated sites to examine the extent to which beach behaviour is coherent over a relatively large region (100-km stretch of coast) and predictably coupled to incident wave forcing. Over the study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 65 publications
4
36
0
Order By: Relevance
“…They found that the recovery mechanisms and timescales were highly dependent on the site characteristics, and that high-energy wave events were essential for the recovery of sediments. Burvingt et al (2018) found that for a number of very similar beaches in southwest England recovery from the 2013-14 storm was regionally coherent, multi-annual (>3 years) and mainly controlled by winter-wave conditions. Castelle et al (2017a) investigated how the beach-dune system of an exposed site in southwest France recovered from winter 2013-14 and found that only after 1.5 years the beach-dune system almost fully recovered to its pre-winter volume.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…They found that the recovery mechanisms and timescales were highly dependent on the site characteristics, and that high-energy wave events were essential for the recovery of sediments. Burvingt et al (2018) found that for a number of very similar beaches in southwest England recovery from the 2013-14 storm was regionally coherent, multi-annual (>3 years) and mainly controlled by winter-wave conditions. Castelle et al (2017a) investigated how the beach-dune system of an exposed site in southwest France recovered from winter 2013-14 and found that only after 1.5 years the beach-dune system almost fully recovered to its pre-winter volume.…”
Section: Introductionmentioning
confidence: 95%
“…Burvingt et al. () found that for a number of very similar beaches in southwest England recovery from the 2013–14 storm was regionally coherent, multi‐annual (>3 years) and mainly controlled by winter‐wave conditions. Castelle et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, during recovery the “usable” width of a beach is restored to satisfy beach goers (Frampton, ) and impacted beach ecology returns to its former state of health (Revell et al, ). While studies have developed empirical and process‐based understanding of storm erosion (e.g., Larson & Kraus, ; Roelvink et al, ), insight into beach recovery and the physical parameters governing the rebuilding of subaerial beach profile is less well observed and understood (e.g., Burvingt et al, ; Corbella & Stretch, ; Dodet et al, ; Jensen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The rebuilding of the berm and beachface by swash processes marks the most landward extent of wave‐driven processes during beach recovery, beyond which more gradual aeolian processes rebuild eroded morphology in the backshore and dunes (Morton et al, ). The majority of previous investigations of swash‐driven beachface (i.e., seaward of the berm crest and extending to mean sea level, MSL) and berm (i.e., landward of the berm crest and seaward of the foredune toe) morphodynamics during recovery are limited by the temporal resolution of poststorm morphology data sets which typically capture morphological and volumetric changes during recovery at monthly to yearly timescales (e.g., Burvingt et al, ; Castelle et al, ; Corbella & Stretch, ; Houser et al, ; Kobayashi & Jung, ; Morton et al, ; Scott et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%